Reinterpreting the French Revolution : a global-historical perspective - Stone, Bailey, 1946- (Cambridge University Press, 2002)
Stone draws on the latest scholarship on diplomatic, political, social, economic, and cultural history of eighteenth-century and revolutionary France to attribute the outbreak of the French Revolution and later developments to pressures of international and domestic politics on those national leaders attempting to govern France and to modernize its institutions.